Pancasila Democracy Between Normative Concepts and Political Practice - Cucu Supyan Cahyana; Ahmad Ahmad; Gamal Abdul Nasir; Franky Aryadi; Rijal Ibnu Sani (Universitas Muhammadiyah Tangerang, 2024)
Pancasila Democracy constitutes Indonesia’s distinctive political system, rooted in the noble values of Pancasila and the 1945 Constitution. Normatively, Pancasila Democracy positions the people as the ultimate holders of sovereignty, implemented through moral principles, social justice, and deliberation to achieve consensus. However, in political practice, the implementation of Pancasila Democracy has frequently deviated from its foundational values. This article aims to analyze the gap between the normative concept of Pancasila Democracy and the realities of political practice in Indonesia across different periods, while also offering reflections and strategic measures to restore its original meaning. The study employs a library research method with a normative and descriptive-analytical approach. The findings indicate that Pancasila Democracy continues to face serious challenges, including the prevalence of transactional politics, weak political ethics, and low levels of morally grounded political participation. Therefore, revitalizing Pancasila values within national political life is an urgent necessity to achieve a democratic system that is just, ethical, and civilized.